2020
DOI: 10.14232/actahisp.2020.25.87-99
|View full text |Cite
|
Sign up to set email alerts
|

La velocidad de articulación en la enseñanza de ELE

Abstract: En la presente investigación se analiza la velocidad de articulación, es decir, la rapidez de la producción de los signos lingüísticos, en el habla semiespontánea. Comparamos la velocidad media de cuatro dialectos del español (madrileño, andaluz, mexicano y rioplatense), para tener la respuesta a la pregunta si se habla más rápidamente en Europa que en América. Además, investigamos la velocidad de articulación de estudiantes hungaroparlantes de nivel B2 para ver si sus valores son más lentos que los de los nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
2
2
1
3
Order By: Relevance
“…These results partly coincide with our previous results (Kovács, 2020) on articulation rate: we compared the articulation rate of four Spanish dialects (Madrilenian, Andalusian, Mexican, and Rioplatense) and found that Andalusian Spanish had the second highest articulation rate (6,42 syllables/second) and Rioplatense Spanish the second lowest articulation rate (6,22 syllables/second). Therefore, we can say that there may be a correlation between articulation rate and total syllable contraction: Andalusian Spanish seems to produce the highest numbers in both variables (first in total syllable contraction and second in articulation rate), while Rioplatense Spanish tends to be associated with lower figures (fourth in total syllable contraction and third in articulation rate).…”
Section: Madrilenian Spanishsupporting
confidence: 91%
See 1 more Smart Citation
“…These results partly coincide with our previous results (Kovács, 2020) on articulation rate: we compared the articulation rate of four Spanish dialects (Madrilenian, Andalusian, Mexican, and Rioplatense) and found that Andalusian Spanish had the second highest articulation rate (6,42 syllables/second) and Rioplatense Spanish the second lowest articulation rate (6,22 syllables/second). Therefore, we can say that there may be a correlation between articulation rate and total syllable contraction: Andalusian Spanish seems to produce the highest numbers in both variables (first in total syllable contraction and second in articulation rate), while Rioplatense Spanish tends to be associated with lower figures (fourth in total syllable contraction and third in articulation rate).…”
Section: Madrilenian Spanishsupporting
confidence: 91%
“…We can see that native-like pronunciation and fluency may have importance even in the avoidance of negative linguistic bias. However, our previous investigations on the speech (Kovács, 2019) and articulation rates (Kovács, 2020) of Hungarian learners showed that in this area, development was needed even at B2 (CEFR) level because Hungarian learners of Spanish produced significantly slower speech and articulation rates compared to native speakers.…”
Section: Introductionmentioning
confidence: 97%
“…Estas cifras son más bajas que la proporción de pausas y titubeos en el húngaro, que es de aproximadamente 20-30% (Gósy, 2004: 209-212). No obstante, nuestros resultados sobre la proporción de pausas y titubeos muestran parcialmente la misma tendencia que experimentamos en el caso de la velocidad de articulación (Kovács, 2020): en esa investigación, la variedad mexicana resultó ser la más rápida (que aquí es el dialecto con la menor proporción de pausas y titubeos) y el madrileño con la velocidad de articulación más baja (aquí con la mayor proporción de pausas y titubeos). Es importante destacar que al calcular la velocidad de articulación, no se tienen en cuenta las pausas y los titubeos (Voigt -Schüppert, 2013: 321;Sjons -Hörberg, 2016).…”
Section: Primera Hipótesisunclassified
“…Sin embargo, como los informantes húngaros de esta investigación estudian el español como lengua extranjera, parece ser problemático aceptar la cifra de arriba en este caso. En un estudio anterior nuestro (Kovács, 2020), medimos la velocidad de articulación de cuatro dialectos del español y de alumnos húngaros de nivel B2 MCERL, y nuestros resultados mostraron una diferencia de al menos 25% entre los nativos y los húngaros. No obstante, la velocidad de articulación excluye las pausas y los titubeos (Gósy, 2004: 203-204), mientras que estos fenómenos los tenemos en cuenta al medir la velocidad de habla.…”
Section: Introductionunclassified
See 1 more Smart Citation